Pengaruh Keterlibatan Karyawan dan Budaya Perusahaan Terhadap Kinerja Perusahaan di Hotel Horizon, Bandar Lampung - Haryono, Joko; Rahmanita, Myrza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
This study aims to analyze the effect of employee involvement and corporate culture on company performance. The research method uses multiple regression analysis. The population in this study were all employees at the Horison Hotel Bandar Lampung. While the sample amounted to 100 respondents. The results of the study partially involve employee involvement and company culture have a significant effect on company performance. Employee involvement at Hotel Horison Bandar Lampung has a positive impact on company performance through high commitment, dedication and enthusiasm in their duties, which increases motivation, productivity, guest service, customer satisfaction and operational efficiency. Corporate culture has a significant influence on the performance of Hotel Horison Bandar Lampung. A strong and clear culture creates stronger identification between employees and company goals, encourages motivation and dedication, and promotes active participation, innovation and collaboration. All of this has a positive impact on the quality of service and the overall guest experience. Hotel Horison Bandar Lampung is expected to create open and effective communication channels between management and employees and focus on developing a positive, inclusive and collaborative corporate culture to enhance employee engagement and overall team spirit. Keywords: Employee engagement, Company Culture, Company Performance